Commodity Markets Evolution, Challenges, and Policies - Baffes, John (The World Bank, 2022)
Commodity markets are integral to the global economy. Understanding what drives developments of these markets is critical to the design of policy frameworks that facilitate the economic objectives of sustainable growth, inflation stability, poverty reduction, food security, and the mitigation of climate change. This study is the first comprehensive analysis examining market and policy developments for all commodity groups, including energy, metals, and agriculture, over the past century. It finds that, while the quantity of commodities consumed has risen enormously, driven by population and income growth, the relative importance of commodities has shifted over time, as technological innovation created new uses for some materials and facilitated substitution among commodities.
Keywords: Agriculture; Climate Change; Commodities; Commodity Markets; Commodity Prices; Economic Growth; Energy; Energy Transition; Metal; Resources; Substitution